The innovation is marvel personal care station / Nur Farahim Aisyah Mohd Razali … [et al.] - Mohd Razali, Nur Farahim Aisyah; Zainal Kharib, Nur Ain; Abd Aziz, Nor Athirah; Mahadi, Nur Hazni; Roslin, Nur Fitri Zawani (2019)
The innovation is Marvel Personal Care Station, a mobile"trolley of personal hygiene kits, which also included automatic water supply, to be used by hospital staff, care giver of bed ridden patient or the patient themselves.